FORMATION OF HEALTH CULTURE - INTEGRATED COMPONENT OF EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
Of the arider “Formation o f health culture is a distinctive part of education”. By doctor of medical sciences, professor of zoology faculty A.P. Aphonin, docent Brusgin V. A . and lectures of zoology faculty Kanelskaya І.M. of Krivoy Rog state Pedagogical University.An important part in bringing up a healthy generation is forming the valeological culture, the need o f leading a healthy way o f life Shod, high school must become a center o f bringing up a health culture.
Keywords: 1